2020
DOI: 10.3390/healthcare8040484
|View full text |Cite
|
Sign up to set email alerts
|

Professional Quality of Life and Perceived Stress in Health Professionals before COVID-19 in Spain: Primary and Hospital Care

Abstract: This study aimed to analyze the professional quality of life and the perceived stress of health professionals before COVID-19 in Spain, in primary and hospital care professionals. A cross-sectional observational study on health professionals working in health centers during the health crisis caused by COVID-19 was conducted. Professional Quality of Life (ProQoL) and Perceived Stress (PSS-14) were measured, along with socio-demographic and labor variables through an online questionnaire. A descriptive and corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
72
4
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 34 publications
11
72
4
11
Order By: Relevance
“…Our results contrast with the high levels of CF and BO perceived in previous studies with health professionals from Spain and Italy [ 33 , 34 ], which are two of the most affected countries in the European Union [ 47 , 48 ]. A possible explanation may be that the present study’s data collection was conducted over three months, in which the information about the development of the health crisis and the measures for its control were advancing.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results contrast with the high levels of CF and BO perceived in previous studies with health professionals from Spain and Italy [ 33 , 34 ], which are two of the most affected countries in the European Union [ 47 , 48 ]. A possible explanation may be that the present study’s data collection was conducted over three months, in which the information about the development of the health crisis and the measures for its control were advancing.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with other research [ 33 , 34 ], female participants showed higher CF levels. This could be explained by the fact that during the time of data collection, women may have sustained a higher emotional and professional burden due to the confinement restrictions, online classes, and workload, given the high number of positive COVID-19 cases in Ecuador at the time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous national and international studies, however, have shown high levels of stress among HCWs, whether in regular conditions or during the COVID-19 pandemic [6,[11][12][13][14][15]. For example, the Middle East Respiratory Syndrome coronavirus (MERS-CoV) has been identified in 2012 in many countries worldwide and most cases were diagnosed in Saudi Arabia [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has three main dimensions, namely compassion satisfaction, job burnout, and secondary traumatic stress 11 . Studies showed that OS had signi cant negative relationship with nurses' quality of work life 12 and the compassion satisfaction dimension of PQOL, while it had signi cant positive relationship with the job burnout and the secondary traumatic stress dimensions of PQOL 13 . On the other hand, staff with low PQOL have poorer organizational identity, job satisfaction, and occupational performance and are more likely to quit their job 14,15 .…”
Section: Introductionmentioning
confidence: 99%